Paradigma Eklektisisme Kewarisan Dayak Ngaju Palangka Raya Kalimantan Tengah - Syaikhu Syaikhu; Norwili Norwili; Rabiatul Adawiyah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2022)
The urgency of this research arises from the existence of the Ngaju Dayak customary inheritance law which has its own characteristics that are unique to Indonesia, which are different from Islamic law and Western law/positive law. This paper will explain a thought that describes the paradigm of eclecticism of the Dayak Ngaju customary inheritance in regulating the various legal systems used by the Dayak indigenous people. The inheritance eclecticism as a form of accommodation for local customs created legal harmonization. The research approach used was qualitative descriptive and the data collection through interviews and field observations. The eclecticism paradigm of Dayak Ngaju traditional inheritance thinks out three concepts. First, the concept of eclecticism in this text is a concept of a mixture of Dayak Ngaju customs. Second, there is a spirit in Islamic law. Third, the concept of Dayak Ngaju traditional inheritance is an open concept with its plural development with the concept of Islamic law inheritance and positive law.Urgensi penelitian ini muncul karena adanya hukum waris adat suku Dayak Ngaju yang memiliki ciri yang unik di Indonesia yang mana berbeda dari hukum Islam maupun hukum Barat/hukum positif. Tulisan ini bertujuan untuk mengetahui sebuah pemikiran yang mendeskripsikan tentang paradigma eklektisime kewarisan adat Dayak Ngaju dalam mengatur berbagai sistem hukum yang dipakai masyarakat adat Dayak. Selain itu, Eklektisisme kewarisan sebagai bentuk akomodir adat lokal sehingga tercipta harmonisasi hukum. Pendekatan yang digunakan adalah deskriptif kualitatif dan pengumpulan data melalui wawancara dan observasi lapangan. Hasil penelitian menunjukkan bahwa Paradigma eklektisisme kewarisan adat Dayak Ngaju melahirkan tiga konsep. Pertama, konsep eklektisisme  dalam teks ini merupakan sebuah percampuran adat Dayak Ngaju. Kedua,  ada semangat dalam hukum Islam. Ketiga, konsep kewarisan adat Dayak Ngaju yaitu konsep terbuka dengan perkembangan pluralnya dengan adanya konsep kewarisan hukum Islam dan hukum positif.